A new species of Ilex (Aquifoliaceae) from Mexico - Lozada-Pérez, Lucio (Phytotaxa, 2019)
A new species of the state of Chiapas, Ilex montebellensis, is herein described and illustrated. The specimens were previously determined as I. mitis, an endemic species of Africa. This new species is morphologically akin to I. tectonica but differs for presenting larger leaves, 9.0‒22.0 × 4.0‒9 cm, petioles 1.5‒4.0 cm, masculine inflorescences in fasciculated dichasia, fruit with hard mesocarp and dorsally smooth pirenes. The checklist of species for Mexico and Mesoamerica is analysed. An identification key with Mesoamerican species that share the entire character of the leaf blade with the new species, is provided.